What's New in Congenital Hand Surgery. Issue 8 (September 2020) - Pino, Paula A.; Zlotolow, Dan A.; Kozin, Scott H.
Abstract : Background: Congenital conditions of the hand and upper extremity are a frequent source of consultation among pediatric orthopaedists and hand surgeons. Advances in the fields of molecular biology and genetics have helped to better understand some of these conditions and redefine previous classification systems. New outcome measurement tools have been used to assess surgical results and have brought into focus a different aspect of the patients' experience. Methods: We searched PubMed database for papers related to the treatment of congenital hand anomalies published from January 1, 2015 to October 31, 2018. The search was limited to English articles yielding 207 papers. Three pediatric hand surgeons selected the articles based upon the criteria that the topic was germane, the article fell under the subheadings within the manuscript, and the conclusions were meaningful. Results: A total of 40 papers were selected for review, based upon their quality and new findings. Research articles with significant findings were included for syndactyly, symbrachydactyly, cleft hand, polydactyly, radial longitudinal deficiency, congenital radio-ulnar synostosis, and macrodactyly. Conclusions: Our knowledge of the embryology and pathophysiology of congenital upper extremity conditions continues to evolve. Functional assessments combined with patient and parent-reported outcomes have our understanding of the results following surgical procedures. Further research and standardization of our scientific data will provide better answers and higher quality of evidence. Level of Evidence: Level V—literature review and expert opinion.